2023
DOI: 10.31458/iejes.1223463
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Technology Pedagogy Content Knowledge Levels of Preservice Mathematics Teachers through Activities

Abstract: It is one of the important qualifications of teachers to know contemporary instructional technologies and to use them in their lessons. However, the studies have concluded that teachers' use of technological tools and equipment is inadequate and their level of using materials is generally not at a desirable level. In this context, the aim of this study is to determine the level of Technological Pedagogical content knowledge of preservice mathematics teachers in the context of technology-supported activities th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Furthermore, research has shown that traditional methods of technology training, such as courses and workshops, are not sufficient for teachers to become brainy users of technology. They need to acquire skills related to the use of technology and learn how to effectively apply and integrate these skills into their instructional practices (Bulut & Güveli, 2023). Therefore, it is crucial for teachers to develop a high level of competence in ICT and have positive attitudes toward its use (Noordan & Yunus, 2022).…”
Section: What Are the Abilities Of Teachers To Use Technology In Clas...mentioning
confidence: 99%
“…Furthermore, research has shown that traditional methods of technology training, such as courses and workshops, are not sufficient for teachers to become brainy users of technology. They need to acquire skills related to the use of technology and learn how to effectively apply and integrate these skills into their instructional practices (Bulut & Güveli, 2023). Therefore, it is crucial for teachers to develop a high level of competence in ICT and have positive attitudes toward its use (Noordan & Yunus, 2022).…”
Section: What Are the Abilities Of Teachers To Use Technology In Clas...mentioning
confidence: 99%